Evaluation of the Antidiarrheal Activity of Aqueous Leaf Extract of Senna surattensis on Castor Oil-Induced Diarrhea in Rats - Ahmed, Maryam Usman; Samson, Mary; Adamu, Yusuf Muhammad (African Journal of Sciences and Traditional Medicine, 2025)
Diarrheal disease is a major health problem in developing countries. It is the second leading cause of death among children under five globally; accounting for about 9 percent of all deaths. This study was aimed at evaluating the antidiarrheal activity of the aqueous leaf extract of Senna surattensis. The antidiarrheal effect of the extract was evaluated using castor oil-induced diarrhea model. Loperamide was used as the standard drug. Thirty (30) Wistar rats were divided into six (6) groups of five (5) rats each. Groups I and II served as the normal and negative controls respectively, group III as standard treatment and groups IV, V and VI as test groups. The extract was administered orally at three different doses of 100 mg/kg, 200 mg/kg and 400 mg/kg to groups IV, V and VI respectively. The extract exhibited a graded dose-dependent inhibition of castor oil-induced diarrhea. The stool inhibition was highly significant at 100 mg/kg (88.1% inhibition) and maximal at 400 mg/kg (100% inhibition). The maximal effect produced by the extract at 400 mg/kg (100% inhibition) is similar to that of the standard drug (5 mg/kg loperamide) which produced 97.6% inhibition. The extract also exhibited a modest dose-dependent reduction on the distance travelled by the charcoal meal. This extract high doses, significantly decrease the volume of the intestinal content when compared to that of the negative control. The results obtained from this study suggests that the aqueous leaf extract of Senna surattensis have significant antidiarrheal effect on animal models and this finding supports the traditional use of this plant extract for treatment and or management of diarrhea.